detection the pathogenicity of Salmonella spp isolated from drinking water in some region of Baghdad city in animal module. (Journal of the College of Basic Education, 2022)
One thousand five hundred sixty seven water samples from different parts of Baghdad city were collected from the beginning of April 2010 till the end of December 2011, all samples were bacteriologically examined by traditional methods for detection of Total coliform and other pathogenic bacteria. Five isolate of Salmonella spp. were isolated and tested for its pathogenicity and ability to toxin production in the mouse module , all environmental isolates induced fluid accumulation (FA ratio≥100) after 5 hours and cause histopathological effects after 24h of inoculation. Histopathological changes showed inflammation of the mucosa and submucosa in the small intestine with mild chronic inflammatory cells and shortanage of villi ,mild degenerative of renal tissue and slightly necrosis, massive necrosis of hepatic cells with infiltrate of mild inflammatory cells in